Isolation and molecular analysis of humic acid-tolerant bacteria that are resistant to pesticides - Chia, Soo Yee (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Twenty two bacterial strains isolated from peat soils in a pineapple plantation were analyzed. Fourteen of the Gram-negative strains were tentatively classified into 12 genera that included Thiobacillus, Acinetobacter, Acidiphilium, Enterobacter, and Pseudomonas. 91% of the isolates were able to tolerate 2,4-dimethylamine with concentrations of up to 10,000 ppm, while 60% of the isolates were resistant to malathion and chlorpyrifos with concentrations of up to 50,000 ppm. As for antibiotics, 82% of the isolates able to survive in carbenicillin agar with concentrations of 1000 ug/ml. 70% of the isolates can survive in both tetracycline and streptomycin media. Four bacterial isolates, C105 (Acidiphilium cryptum), C102 (Sulpholobus spp), C108 (Leptospirillum spp) and Y104 (Pseudomonas flouresc/putida) that were pesticide resistant were analyzed for the presence of plasmid. No plasmid was detected in antibiotic resistant isolates except for strains designated as Y 103 and C 105. The sizes of the isolated plasmids were estimated ranging from 6 kb to 54 kb. Further studies are required to investigate the genes which confer resistance properties in the acidophiles.